Annual General Meeting of the Institute (The Southern African Institute of Mining and Metallurgy, 1981)
The Annual General Meeting of the South African Institute of Mining and Metallurgy was held in Kelvin House, Johannesburg, on Wednesday, 19th August, 1981. Dr P. R. Jochens (President) was in the chair and declared the meeting open at 4.05 p.m. This account of the proceedings includes only those matters that are not reported under the heading `Annual report and accounts' elsewhere in this issue. Confirmation of the Minutes The minutes of the last Annual General Meeting, which was held on 27th August, 1980, were confirmed as pub¬lished in the September issue of the Journal. Welcome President: I extend a sincere welcome to you all, especially to the following distinguished guests: Mr L. W. P. van den Bosch, President of the Chamber of Mines, and Mrs van den Bosch; Mr J. G. Kirchner, Government Mining Engineer, and Mrs Kirchner; Dr William Ble¬loch; Dr L. Alberts, President of the National Institute for Metallurgy, and Mrs Alberts; Dr C. F. Habis, Presi¬dent of the CSIR, and Mrs Habis; Dr P. J. Hugo, Chief Director of the Minerals Bureau, and Mrs Hugo; Mr D. N. Stuart, General Manager of the Chamber of Mines, and Mrs. Stuart; the Presidents and representatives of other Institutes and their wives; and Honorary Life Fellows of our Institute and their wives.